Integrating Learning Analytics, AI, and STEM Education: : A Comprehensive Review - Kim, Tai Ki (International Journal of Research in STEM Education, 2024)
This paper presents a comprehensive review of the integration of Learning Analytics (LA), Artificial Intelligence (AI), and STEM education within classroom settings, aimed at enhancing educational outcomes. By examining the synergistic effects and interactions among LA, AI, and STEM disciplines, this review highlights how these technologies can collectively transform educational practices. It discusses the potential of LA and AI to personalize learning experiences, thereby improving engagement and academic success in STEM subjects. The paper also explores various case studies and success stories, illustrating practical implementations and the significant impact these technologies have made in schools. Additionally, it addresses the challenges and considerations related to the ethical use of AI and data privacy, providing insights into how educators and policymakers can navigate these issues. Overall, this review underscores the critical role of technology in shaping the future of education by fostering more adaptive and inclusive learning environments.